Metode Sayyid Quthb dalam menafsirkan ayat-ayat mengenai kepemilikan dan harta (pembacaan terhadap Tafsir Fî Zhilâl al-Qur'ân) - Mujiatun Ridawati; Muhamad Johari (Journal of Enterprise and Development (JED), 2019)
Revelation in the form of a holy book (al-Qur'an) is often addressed to all humans, regardless of their circumstances or mindsets. Thus, it is entirely conceivable and even necessary for the creation of numerous distinct interpretations. One straightforward and obvious conclusion from these varied readings is that humans have an unequal capacity to comprehend the essence of revelation. It can be argued that Sayyid Quthb's thoughts are difficult to comprehend unless one is willing to read them thoroughly and possesses adequate language skills. Sayyid Quthb employs the tafsr bi ar-ra'yi method, in which he defines property as "everything that can be utilised by humans in carrying out their duties as creatures of Allah." According to Sayyid Quthb, property belongs to Allah swt. entirely, regardless of its form. According to Sayyid Quthb, jihad is an aggressive war waged against Islam's physical adversary through a complete separation of Muslim and non-Muslim ties. According to the preceding definition of jihad, Sayyid Quthb assumes that wealth is merely a tool to be employed in the service of Allah during jihad.